Asia's New Mothers : Crafting gender roles and childcare networks in East and Southeast Asian societies. - Ochiai, Emiko, 1958-; Molony, Barbara (BRILL, 2008)
Through a focus on childcare, this offers a comparative regional analysis unique in English-language sources of changing gender roles in Asia. Taking into consideration the historical and cultural differences and similarities among the societies in the region, the authors employ indepth researches of people's everyday experiences.